Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Ask your questions and receive accurate answers from professionals with extensive experience in various fields on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
[tex]6x^3-9x^2-12x=x(6x^2-9x-12)=\\\\Finding\ roots\ of\ equation:\\6x^2-9x-12=0\\\\
\Delta=b^2-4ac\\\\a=6,\ b=-9,\ c=-12 \\\\\Delta=(-9)^2-4*6*(-12)=81+288=369\\\\ \sqrt{\Delta}=3\sqrt{41}\\\\x_1=\frac{-b-\sqrt{\Delta}}{2a}\ \ x_1=\frac{9-3\sqrt{41}}{2*6}=\frac{3-\sqrt{41}}{4}\\x_2=\frac{-b+\sqrt{\Delta}}{2a}\ \ x_2=\frac{9+3\sqrt{41}}{2*6}=\frac{3+\sqrt{41}}{4}\\
6x^2-9x-12=(x-\frac{3+\sqrt{41}}{4})(x-\frac{3-\sqrt{41}}{4})[/tex][tex]so \\\\ \textbf{Answer} \\ 6x^3-9x^2-12x=x(6x^2-9x-12)=\\
\underline{x(x-\frac{3+\sqrt{41}}{4})(x-\frac{3-\sqrt{41}}{4})}[/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.